Pendekatan Data Panel Dalam Menganalisis Pertumbuhan Ekonomi di Pulau Jawa - Andika Yusni Mubaroh; Safaat Yulianto (Jurnal Riset Statistika, 2025)
Abstract. Java Island provides the largest economic contribution in Indonesia through the Gross Regional Domestic Product (GRDP) indicator. According to BPS, Java Island accounts for 61.67% of Indonesia's overall GRDP, making it the island with the largest industrial output. The purpose of this study is to analyze the economic development of Java Island and identify the factors that influence it in order to know what factors are influential so that they can be used to develop other islands. GRDP data and variables Life Expectancy, Poverty Rate, Minimum Wage, and Open Unemployment Rate. The method used is Panel Data Regression with 3 models, namely CEM, FEM, and REM. The CEM model is a model that generalizes each individual and time, the FEM model is a model that distinguishes the characteristics of each individual, while REM is a model whose characteristics are random, and uses error terms In the test conducted, only three variables have a relationship, namely the Open Unemployment Rate, Minimum Wage and Poverty Level so that only these three variables are used in further tests. In the test conducted, the best model obtained is the Random Effect Model (REM) with the influential variables being the Open Unemployment Rate and Minimum Wage, it is expected that the results of this study can contribute to economic development in Java and Indonesia.  Abstrak. Pulau Jawa memberikan kontribusi ekonomi terbesar di Indonesia melalui indikator Produk Domestik Regional Bruto (PDRB). Menurut BPS, Pulau Jawa menyumbang 61,67% dari keseluruhan PDRB Indonesia. Tujuan dari penelitian ini untuk menganalisis perkembangan ekonomi Pulau Jawa dan mengidentifikasi faktor-faktor yang berpengaruh sehingga dapat dipakai untuk mengembangkan pulau lainnya. Data PDRB serta variabel Angka Harapan Hidup, Tingkat Kemiskinan, Upah Minimum, dan Tingkat Pengangguran Terbuka. Metode yang digunakan adalah Regresi Data Panel dengan 3 model, yaitu CEM, FEM, dan REM. Model CEM merupakan model dengan tidak ada perbedaan antara tiap individu dan waktu, model FEM merupakan model yang membedakan karakteristik tiap individu, sedangkan REM merupakan model yang karakteristiknya acak, dan menggunakan error terms. Hasil yang diperoleh terdapat tiga variabel yang memiliki hubungan yaitu Tingkat Pengangguran Terbuka, Upah Minimum dan Tingkat Kemiskinan sehingga hanya tiga variabel tersebut yang digunakan dalam uji selanjutnya. Berdasarkan hasil pengujian didapat model terbaik adalah Random Effect Model (REM) dengan variabel yang berpengaruh adalah Tingkat Pengangguran Terbuka dan Upah Minimum, sehingga dapat memberikan kontribusi bagi pembangunan ekonomi di Pulau Jawa dan Indonesia.